ANALISIS SENSITIVITAS USAHATANI KARET (HEVEA BRASILIENSIS. MUELL. ARG) RAKYAT DI KECAMATAN GALANG KABUPATEN DELI SERDANG - Zeta Novia Ramadhan; Rini Mastuti; Supristiwendi (Jurnal Cakrawala Ilmiah, 2023)
This study aims to analyze the sensitivity of rubber farming to acceptance, income and feasibility of rubber farming in Galang District, Deli Serdang Regency. Researchers took 33 samples from the population using the slovin formula and taking samples with the sample random sampling technique. The data used in this research are primary data and secondary data. The results showed that the average total revenue for rubber farming was Rp. 13,937,848 with an average rubber farming income of Rp. 11,383,750 and the average feasibility R/C ratio for rubber farming was 5.6, which means that rubber farming in Galang District is feasible to run because it can provide benefits during farming. The level of sensitivity analysis is based on two scenarios, namely an increase in production costs and a decrease in price with a sensitivity level of 10%, 15% and 20% on the acceptance, income and feasibility of rubber farming in the area. The results of the analysis show that the sensitivity that occurs still provides benefits for farmers in Galang District, Deli Serdang Regency.